(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Background: Simple, sensitive, and dynamic markersfor prediction of outcome, which generate rapidand reliable results, are desirable in critical care units. Aim: Evaluation of prediction of outcome in critically ill patients by the Albumin Creatinine Ratio (ACR)on admission (ACR-1) and after 24hours of admission (ACR-2) & making a comparison between AcutePhysiology & Chronic Health Evaluation-II(APACHE-II), ACR-1 & ACR-2 in terms of outcome prediction. Settings and Study design: The prospective, observational study was carried out in the 20 bed mixedMedical-Surgical ICU of Dhaka Medical College Hospital. Materials and Methods A total 60 critically ill patient were purposively recruited. Adult patient withICU stay of more than 24 hours were included &patients with pregnancy, menstruation, a macroscopichematuria, pre-existing kidney diseases, were excluded in this study. For disease severity scoring, APACHEIIscores & the percentage (%) of prediction of mortality by APACHE-II scores were calculated from datacollected during the first 24 hours following ICU admission. Spot urine samples were collected within 6hrs of admission (ACR1) and again at 24 hrs(ACR2), for quantification of Albumin Creatinine Ratio.Patients were followed up throughout their ICU stay for a maximum of 15 days and the following outcomedata were obtained: ICU length of the stay and ICU mortality. Results: There were 32(53.3%) patients were non-survivors and 28(46.7%) patients were survivors.Non-survivors had a significantly higher median Albumin Creatinine Ratio 1(ACR1) =285.00 mg/g &higher median Albumin Creatinine Ratio 2(ACR2) =393.30 mg/g in comparison to the survivors. Therewere significant differences between the mean and Standard Deviation of the APACHE-II scores, theAlbumin Creatinine Ratio 1(ACR1),the Albumin Creatinine Ratio 2(ACR2)&ACR2-ACR1 between thenon survivors (p=<0.001,p=<0.001,p=<0.001, p=<0.001 respectively). In, multiplelogistic regressionsanalysis female sex scored high odds of 361 for mortality compared to males followed by 15% highermortality by high ACR2.The strength of agreement among APACHEII, ACR1, and ACR2 by kappastatistics revealed a very good agreement (1.000) by the degree of change of ACR2 in comparison toACR1 and APACHE-II Score in predicting outcome in critical ill patients. A good agreement revealedbetween ACR1 and the APACHEII Score (0.802), and The APACHEII Score revealed a fair agreement(0.798) in predicting outcome. Results of all the variables were highly significant. Conclusion: Theraised Albumin- Creatinine Ratio at 24 hours of ICU admission(ACR2) is a predictor of poor outcomein critically ill patients. JBSA 2018; 31(1): 20-28